Features of microcirculation in younger schoolchildren in the period of early convalescence of acute respiratory viral infections - Levchin, A. M.; Еrshova, I. B.; Glushko, Yu. V. (Medicinskij sovet, 2025)
Introduction . With insufficient oxygen concentration and changes in the blood circulation of microvessels, the processes of transcapillary gas exchange and the supply of energy substances to tissues deteriorate, which leads to disruption of the mechanisms of vascular autoregulation. Aim. To study the features of microcirculation in the period of convalescence of ARVI in primary school children who have started classes. Materials and methods. A prospective comparative study was conducted at the State Budgetary Healthcare Institution “Leningrad City Children’s Hospital No. 1” of the LPR in the period from 2019 to 2024. 246 children aged 7–10 years (average age 8.4 ± 0.5 years) who resumed the educational process after acute respiratory viral infections were examined. Of these, 119 were boys and 127 were girls. Perfusion indices, standard deviation of blood flow oscillation amplitude and variation coefficient were determined depending on the etiology of respiratory disease using laser Doppler flowmetry. Results . A decrease in the arithmetic mean values of skin perfusion was recorded both immediately after discharge from the hospital (by 23.93 ± 3.71%), and a month later (by 20.58 ± 0.34%) and 2 months later (by 13.9 ± 2.57%) after resumption of school, compared to healthy subjects. The severity of the disorders depended on the pathogen and were more often recorded during the recovery period of COVID-19 and infectious mononucleosis. Prolongation of microcirculatory disorders was recorded up to 5 months after returning to school. The pathological form of microcirculation was determined in 64.41% of children, with the registration of the hyperemic type. Conclusions. A decrease in perfusion parameters and deviations in perfusion fluctuations were significantly more often observed during the convalescence period after infectious mononucleosis and COVID-19. A decrease in the contribution of active regulatory systems of microcirculation was noted against the background of impaired trophism in tissues.